Faktor yang Mempengaruhi Perilaku Keberagamaan Anak : Analisis Terhadap Anak yang Ayahnya Merantau - Muhamad Yahya (Institut Darul Quran Payakumbuh, 2014)
Minangkabau people have a culture of going far away for earning their lives. Generally, they go outside with their family, while some others leave their family in the village. This culture impacts on their family especially in exploring their children’s characteristics that live with single parent, even with their grandparents. As a result, many of them get bad development in their lives particularly in social behavior and religion application. In this article, the writer analyzes on the development of children whose fathers are going far away for earning their lives, but they show good social behavior and religion application. The data are taken from the children in the subdistrict of Suayan, Lima Puluh Kota Regency. The analysis includes prayers five times a day, reading Holly Qur’an, and social manner toward their friends and parents. In doing the research, the writer uses qualitative descriptive method.This research shows that the children whose fathers go far way for earning their lives, show good social manner and religion application. It is proved by their behavior in four aspects told above which are influenced by several factors. Those are the guidance of their mothers, grandparents, siblings as well as their teachers both at schools and at Qur’an learning centres, called TPA